Character Presentation in Jaber Khalifa Jaber's narrative (Journal of the College of Basic Education, 2026)
The fictional character forms the central axis of the novelistic work، due to its paramount importance in managing the course of the narrative text، as it represents the driving force that enhances the charging of the rest of the elements in the narrative system. Thus، the character appears as an objective equivalent to the entire novel and the dominate element around which the structure of the event is centered and from which it takes it's direction and structural mood، For example، a character's emotional behavior of enhances the semantic weight of the narrative structure and interactively illuminates it's narrative pattern. This necessitates that the writer to seize the character's situational moment and identify with them as beings with their own independent existence، avoiding abrupt appearance that disrupts the central plot، The novelist must therefore exercise caution، Projecting an unspoken dominance and examining their characters، their expressive temperament، and their psychological convictions، all in accordance with the narrative concept and semantic intentions in this research. we attempt to approach the novelist (Jaber Khalifa Jaber)'s Presentation of his characters in an important novel، namely the novel (The Camp of the Muarka)، and how he furnished their material aspect، as well as deconstructing their psychological structure and reshaping it within the framework of the narrative plot.